Atmospheric Attenuation Analysis Using Aldo-Alphasat Beacon Signal in Prague - Pek, Viktor; Fišer, Ondřej (IEEE, 2017)
In this contribution we describe selected attenuation events recorded by the "Alphasat" satellite receiver at the Institute of Atmospheric Physics (IAP) in Prague. First of all we compare the attenuation course and the rain rate course - good correlation was acknowledged. Also the cumulative distribution of attenuation for September 2015 and more months together (September - June, 2016) is demonstrated. Some selected rain attenuation prediction methods were used to compare measured and computed attenuation which is, in fact, caused by rain mainly. We added frequency scaling description and test of the ITU-R scaling method of quite good result related to peak attenuation values.
Analýza atmosférického útlumu majákového signálu Aldo-Aphasat v Praze
Keywords: Alphasat; radiowave propagation; atmospheric attenuation; satellite link; Alphasat; šíření rádiových vln; atmosférický útlum; družicový spoj